Hyperreality in Ecological Crisis: Postmodern Representation of Climate Change, Life Below Water and Life on Land in Lil Dicky’s Earth - Mesqia Putri Perbina (Jurnal Bahasa, Sastra, dan Studi Amerika, 2026)
The role of literature in human life is inseparable from the process of forming thoughts, feelings and an understanding of reality. In its development, literature does not exist in isolation but is always linked to the times and prevailing currents of thought. Second, this song also blurs the line between entertainment and social criticism. The characteristics of postmodernism can be found in various fields, including art, literature and popular culture. The relationship between postmodernism and literature becomes even more intriguing when literary works appear not only in conventional forms such as novels or poetry, but also in more popular forms, such as songs. One example of a work that can be analysed within this framework is Lil Dicky’s song “Earth.” The song was created to raise awareness of the importance of protecting the environment and addressing the climate crisis. From a literary perspective, Earth employs personification as one of its primary devices. From a postmodern perspective, “Earth” exhibits several distinctive characteristics. Second, this song also blurs the line between entertainment and social criticism. In addition, “Earth” can also be linked to the discourse on sustainable development as articulated in the Sustainable Development Goals (SDGs).